Improving well-being through psycho-education among voluntary counseling and testing seekers in Nigeria: A controlled outcome study (2006)
The present study evaluated the efficacy of an individualized psycho-education (PE) program in reducing psychological distress and risky sexual behavior and enhancing self-disclosure associated with an HIV diagnosis among attendees of a walk-in non-governmental voluntary counseling and testing (VCT) center in Nigeria. Ninety-four consecutive individuals were asked to complete a pre-counseling, baseline questionnaire detailing their sociodemographic characteristics, psychopathology, sexual practices, self-disclosure intention and coping behaviors. They were screened for HIV and posttest counseled. Sixty-seven individuals (72.2%) who tested positive were consecutively randomly assigned to one of two groups: a PE program (four 60-minute weekly manual driven sessions) (N= 34) and a wait-list (WL) control group (N= 33). The major outcome measures used were the Crown Crisp Experiential Index (CCEI), the Beck Depression Inventory (BDI) (Beck et al., (1961), self-report sexual practices in past three months, self-disclosure intention and the brief COPE. At four weeks post-intervention, significant reductions on all measures as well as reduction in risky sexual practices were observed in the treatment group compared with the wait-list group. Treatment group members were also significantly more likely to disclose their serostatus and accept their HIV status as a way of coping, compared with the wait-list group. Overall, support was found for the efficacy of a manual-driven PE program for self-disclosure, reduction of depression and improvement in safe sexual practices.